SnTe-based thermoelectric material with multi-scale nanocomposite structure and preparation method thereof

By doping Y and Cu2Te in SnTe to form a multi-scale nanocomposite structure, the problem of the small thermoelectric superiority ZT of the existing SnTe-based thermoelectric materials is solved, and the Seebeck coefficient and thermoelectric superiority ZT are significantly improved, and the thermoelectric performance is improved.

CN116903370BActive Publication Date: 2025-03-04JIANGSU WANXIN OPTICAL +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310644133.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-03-04
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The thermoelectric superiority ZT of existing SnTe-based thermoelectric materials is small, the thermoelectric performance needs to be optimized, and the Seebeck coefficient is not high.

Method used

By doping rare earth elements Y and Cu2Te at a specific concentration in SnTe, a SnTe-based thermoelectric material with a multi-scale nanocomposite structure is formed. The method includes the steps of flame sealing pipe under the protection of an inert gas, high-temperature melting reaction, quenching, high-temperature annealing and discharge plasma sintering.

Benefits of technology

The Seebeck coefficient and thermoelectric superiority ZT of SnTe-based thermoelectric material are significantly improved, and the ZT value at 823K reaches ~1.27, which improves the thermoelectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903370B_ABST
    Figure CN116903370B_ABST
Patent Text Reader

Abstract

The present invention discloses a SnTe-based thermoelectric material and a preparation method thereof, and relates to the field of thermoelectric materials, and in particular to a SnTe-based thermoelectric material with a multi-scale nanocomposite structure and a preparation method thereof. 1‑x Y x Te-5%Cu2Te, wherein x is 0, 0.01, 0.03, 0.05 or 0.07, which is prepared by using a high-purity metal element as a raw material, according to the stoichiometric ratio of the chemical formula, and after vacuum flame sealing, melt reaction quenching, and high temperature annealing, it is ground into powder, and vacuum discharge plasma sintering is performed to obtain a bulk SnTe-based thermoelectric material. Compared with the prior art, the present invention optimizes the hole carrier concentration and band structure of the SnTe material by co-doping SnTe with Cu and Y. At the same time, increasing the Y solid solubility allows the in-situ formation of a multi-scale nanostructure in SnTe, further reducing its thermal conductivity, thereby greatly improving the thermoelectric performance of the SnTe material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy material science and technology, and in particular to a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure. Background Art

[0002] Thermoelectric materials play a key role in the development of sustainable energy-saving technologies. Thermoelectric devices can directly convert thermal energy into electrical energy using thermoelectric power generation. Thermoelectric power generation is a fully static direct power generation method that uses thermoelectric conversion materials to convert thermal energy into electrical energy. In theory, these thermoelectric devices can use any heat source, including solar energy and waste heat, and their energy cleanliness characteristics have always attracted widespread attention. In addition, these thermoelectric devices have the advantages of reliable performance, no noise, no wear, no leakage, and flexible mobility, and are used in many fields such as aerospace, medicine, and microelectronics.

[0003] The conversion efficiency of thermoelectric materials is determined by the figure of merit ZT = S 2 σT / (κ e +κ lat ) is evaluated, where S, σ, T, κ e and κ lat They are Seebeck coefficient, electrical conductivity, absolute temperature, carrier thermal conductivity and lattice thermal conductivity. However, the mutual coupling relationship between these parameters hinders the realization of high ZT values.

[0004] SnTe-based thermoelectric materials are non-toxic and easy-to-prepare medium-temperature TE materials, and have been successfully applied in deep space exploration, waste heat recovery and other fields. Since they have the same crystal structure and similar band structure as PbTe and are environmentally friendly, they are widely used as potential substitutes for toxic PbTe. However, due to the large number of intrinsic Sn vacancies in SnTe, which leads to high hole carrier concentration, low Seebeck coefficient and relatively high electronic thermal conductivity, its intrinsic SnTe thermoelectric performance is poor. The introduction of some non-intrinsic elements can effectively reduce the thermal conductivity of SnTe, thereby improving its thermoelectric figure of merit. Existing studies have shown (Interstitial Point Defect Scattering Contributing to High Thermoelectric Performance in SnTe. Advanced Electronic Materials, 2016, 2. DOI: 10.1002 / aelm.201600019) that SnTe solid solution cuprous telluride (Cu2Te) can form a large number of interstitial copper defects, and the strong phonon scattering mechanism of interstitial copper greatly reduces the lattice thermal conductivity. Although this work effectively reduces the thermoelectric rate of the SnTe system and improves its thermoelectric performance to a certain extent, the overall Seebeck coefficient has not been significantly improved, the thermoelectric figure of merit ZT is still small, and the thermoelectric performance needs to be optimized. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the object of the present invention is to provide a SnTe-based thermoelectric material which is directly used for thermoelectric mechanism research, has a simple preparation process, a short experimental cycle, and a large improvement in thermoelectric figure of merit.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure, comprising the following steps:

[0008] S1: Under inert gas protection, chemical formula Sn 1-x Y x The stoichiometric ratio of Te-5%Cu2Te is obtained by weighing the metal single substance raw materials Te, Sn, Cu and Y, wherein x is 0, 0.01, 0.03, 0.05 or 0.07, and then the single substance materials are mixed evenly and transferred to a quartz tube, and the tube is flame-sealed in a vacuum environment using a hydrogen-oxygen machine;

[0009] S2: Under vacuum conditions, the quartz tube vacuum-packed in S1 is heated in a box furnace to allow the raw materials to fully react in a high-temperature molten state, and then quenched to obtain an ingot;

[0010] S3: Under vacuum conditions, the ingot of S2 is reheated for high temperature annealing;

[0011] S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintered under certain conditions to obtain a high-density bulk SnTe-based thermoelectric material;

[0012] Furthermore, in S1, the purity of each metal element is not less than 99.999%;

[0013] Furthermore, in S2, the process conditions of the melting reaction include: within 6 to 8 hours, the temperature in the quartz tube is raised from room temperature to 1200K to 1300K, and the temperature is kept for 8 to 12 hours. After the temperature is kept, the quartz tube is immediately placed in supersaturated brine at room temperature for quenching; preferably, the temperature is raised to 1273K; preferably, the temperature is kept for 10 hours;

[0014] Further, in S3, the annealing process includes: within 3 to 5 hours, raising the temperature of the quartz tube from room temperature to 900 to 950K, keeping the temperature for 1 to 3 days, and then lowering the temperature to room temperature; preferably, the temperature is raised to 1273K; preferably, the temperature is kept for 3 days;

[0015] Further, in S4, the spark plasma sintering process includes: evacuating the reaction system, and then sintering for 3 to 10 minutes under Ar protection at a temperature of 773K to 823K and a pressure of 45 to 55MPa; preferably, the temperature is 823K; preferably, the pressure is 50MPa; preferably, the sintering time is 5 minutes.

[0016] Beneficial Effects

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0018] The present invention further doped a specific concentration of rare earth element Y based on the research of specific solid concentration of Cu2Te in SnTe. With the addition of Y, on the one hand, Y fills Sn vacancies to reduce the hole carrier concentration, and at the same time reduces the energy offset between the light and heavy hole valence bands to a certain extent, thereby improving the Seebeck coefficient in the entire measurement temperature range; on the other hand, microstructural characterization shows that in the Y high doping system, Y exists in SnTe as an in-situ grown Y2Te3 multi-scale nano second phase structure, and these multi-scale nanostructures are very conducive to phonon scattering enhancement, which further significantly reduces the lattice thermal conductivity of the compound. Finally, in the case of a nominal composition of Sn 0.97 Y 0.03 In the Te-5%Cu2Te sample, a peak zT value of ~1.27 was obtained at 823K, which greatly improved the thermoelectric performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The curve diagram of Seebeck coefficient and ZT value of SnTe-y%Cu2Te with different compositions as a function of temperature;

[0020] Figure 2 For different components Sn 1-x Y x XRD pattern of Te-5%Cu2Te;

[0021] Figure 3 Sn 1-x Y x The temperature dependence curve of the resistivity of Te-5%Cu2Te;

[0022] Figure 4 Sn 1-x Y x The Seebeck coefficient of Te-5%Cu2Te is plotted against temperature;

[0023] Figure 5 Sn 1-x Y x Room temperature carrier concentration and mobility of Te-5%Cu2Te as a function of Y content;

[0024] Figure 6 Sn 1-x Y x The power factor of Te-5%Cu2Te is dependent on temperature;

[0025] Figure 7 Sn 0.97 Y 0.03 FSEM photo of the free fracture surface of Te-5%Cu2Te bulk product at high magnification;

[0026] Figure 8 Sn 1-x Y x The total thermal conductivity and lattice thermal conductivity of Te-5%Cu2Te are plotted against temperature;

[0027] Fig. 9 Sn 1-x Y x Temperature dependence of ZT value of Te-5%Cu2Te. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0029] Example 1

[0030] A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure comprises the following steps:

[0031] S1: Under the protection of inert gas, weigh the metal single substance raw materials Te, Sn, Cu and Y according to the stoichiometric ratio of the chemical formula SnTe-5%Cu2Te, and the purity of each metal single substance is not less than 99.999%. Then, mix the single substance materials evenly and transfer them to a quartz tube, and use a hydrogen-oxygen machine to flame seal the tube under a vacuum environment; S2: Heat the vacuum-sealed quartz tube in S1 in a box furnace to make the raw materials fully react in a high-temperature molten state, and then quench to obtain an ingot. Within 8 hours, heat the quartz tube from room temperature to 1280K, keep it warm for 8 hours, and after the insulation is completed, immediately quench it with water to room temperature to obtain an ingot;

[0032] S3: Under vacuum conditions, the ingot of S2 is reheated again for high-temperature annealing. The annealing process includes: within 5 hours, the quartz tube is heated from room temperature to 920K, kept warm for 3 days, and then cooled to room temperature; S4: The ingot obtained from S3 is fully ground into fine powder, and then spark plasma sintered under absolute vacuum at a sintering temperature of 823K, a pressure of 50MPa, and a time of 5min, to obtain a high-density bulk thermoelectric material. Further, in S3, the annealing process includes: within 3 to 5 hours, the quartz tube is heated from room temperature to 940K, kept warm for 3 days, and then cooled to room temperature; S4: The ingot obtained from S3 is fully ground into fine powder, and then spark plasma sintered under absolute vacuum at a sintering temperature of 800K, a pressure of 50MPa, and a time of 5min, to obtain a high-density bulk thermoelectric material.

[0033] Example 2

[0034] A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure comprises the following steps:

[0035] S1: Under inert gas protection, according to the chemical formula Sn 0.99 Y 0.01The stoichiometric ratio of Te-5%Cu2Te is 1: weigh the metal raw materials Te, Sn, Cu and Y, and the purity of each metal single substance is not less than 99.999%. Then, mix the single materials evenly and transfer them to a quartz tube. Use a hydrogen-oxygen machine to flame seal the tube under vacuum. S2: Heat the vacuum-sealed quartz tube in S1 in a box furnace to make the raw materials fully react in a high-temperature molten state, and then quench to obtain an ingot. Heat the temperature in the quartz tube from room temperature to 1280K within 6 hours, and keep it warm for 8 h, after the insulation is completed, immediately quench with water to room temperature to obtain an ingot; S3: under vacuum conditions, the ingot of S2 is reheated again for high-temperature annealing, and the annealing process includes: within 3 hours, the quartz tube is heated from room temperature to 920K, kept warm for 3 days, and then cooled to room temperature; S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintering is performed under absolute vacuum at a sintering temperature of 820K, a pressure of 50MPa, and a time of 5min to obtain a high-density bulk thermoelectric material.

[0036] Example 3

[0037] A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure comprises the following steps:

[0038] S1: Under inert gas protection, according to the chemical formula Sn 0.97 Y 0.03 The stoichiometric ratio of Te-5%Cu2Te is 5%. Weigh the metal raw materials Te, Sn, Cu and Y. The purity of each metal is not less than 99.999%. Then, mix the materials evenly and transfer them to a quartz tube. Use a hydrogen-oxygen machine to flame seal the tube under vacuum. S2: Heat the vacuum-sealed quartz tube in S1 in a box furnace to make the raw materials fully react in a high-temperature molten state, and then quench to obtain an ingot. Heat the temperature in the quartz tube from room temperature to 1275K within 8 hours, and keep it warm for 8 hours. h, after the insulation is completed, immediately quench with water to room temperature to obtain an ingot; S3: under vacuum conditions, the ingot of S2 is reheated again for high-temperature annealing, and the annealing process includes: within 5 hours, the quartz tube is heated from room temperature to 923K, kept warm for 3 days, and then cooled to room temperature; S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintering is performed under absolute vacuum at a sintering temperature of 820K, a pressure of 50MPa, and a time of 5min to obtain a high-density bulk thermoelectric material.

[0039] Example 4

[0040] A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure comprises the following steps:

[0041] S1: Under inert gas protection, according to the chemical formula Sn 0.95 Y 0.05The stoichiometric ratio of Te-5%Cu2Te is 1: weigh the metal raw materials Te, Sn, Cu and Y, and the purity of each metal single substance is not less than 99.999%. Then, mix the single materials evenly and transfer them to the quartz tube. Use the hydrogen-oxygen machine to flame seal the tube under vacuum environment; S2: heat the vacuum-sealed quartz tube in S1 in a box furnace to make the raw materials fully react in the high-temperature molten state, and then quench to obtain the ingot. Heat the temperature in the quartz tube from room temperature to 1273K within 7 hours, and keep it warm for 10 h, after the insulation is completed, immediately quench with water to room temperature to obtain an ingot; S3: under vacuum conditions, the ingot of S2 is reheated again for high-temperature annealing, and the annealing process includes: within 5 hours, the quartz tube is heated from room temperature to 923K, kept warm for 3 days, and then cooled to room temperature; S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintering is performed under absolute vacuum at a sintering temperature of 823K, a pressure of 50MPa, and a time of 5min to obtain a high-density bulk thermoelectric material.

[0042] Example 5

[0043] A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure comprises the following steps:

[0044] S1: Under inert gas protection, according to the chemical formula Sn 0.93 Y 0.07 The stoichiometric ratio of Te-5%Cu2Te is 1: weigh the metal raw materials Te, Sn, Cu and Y, and the purity of each metal single substance is not less than 99.999%. Then, mix the single materials evenly and transfer them to the quartz tube. Use the hydrogen-oxygen machine to flame seal the tube under vacuum environment; S2: heat the vacuum-sealed quartz tube in S1 in a box furnace to make the raw materials fully react in the high-temperature molten state, and then quench to obtain the ingot. Heat the temperature in the quartz tube from room temperature to 1273K within 8 hours, and keep it warm for 10 h, after the insulation is completed, immediately quench with water to room temperature to obtain an ingot; S3: under vacuum conditions, the ingot of S2 is reheated again for high-temperature annealing, and the annealing process includes: within 5 hours, the quartz tube is heated from room temperature to 920K, kept warm for 3 days, and then cooled to room temperature; S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintering is performed under absolute vacuum at a sintering temperature of 823K, a pressure of 55MPa, and a time of 5min to obtain a high-density bulk thermoelectric material.

[0045] Experimental example

[0046] Experimental Example 1: Screening of Substrate SnTe-5%Cu2Te

[0047] In order to compare the chemical properties of the material of the present invention, the chemical formulas of SnTe, SnTe-3%Cu2Te, SnTe-5%Cu2Te, and SnTe-7%Cu2Te were taken and prepared according to the following method to obtain bulk materials of SnTe-y%Cu2Te (y=0, 3, 5, 7, 9) with different concentrations. The preparation method is as follows:

[0048] S1: Under an inert gas environment, weigh the metal raw materials Te, Sn, and Cu according to the stoichiometric ratio of the chemical formula SnTe-y%Cu2Te (y=0, 3, 5, 7, 9), and the purity of each metal single substance is not less than 99.999%. Then, mix the single materials evenly and transfer them to a quartz tube. Use a hydrogen-oxygen machine to flame seal the tube in a vacuum environment where the absolute vacuum degree is not greater than 0.1Pa; S2: Heat the vacuum-sealed quartz tube in S1 from room temperature to 1273 in a box furnace within 8 hours. K, keep warm for 10 hours, and immediately quench with water to room temperature to obtain an ingot after the end of the heat preservation; S3: reheat the ingot of S2 for high temperature annealing, the annealing process comprising: within 5 hours, raising the quartz tube from room temperature to 923K, keeping warm for 3 days, and then cooling down to room temperature; S4: fully grinding the ingot obtained in S3 into fine powder, and then performing spark plasma sintering under absolute vacuum at a sintering temperature of 823K, a pressure of 50MPa, and a time of 5min to obtain a high-density SnTe-based bulk thermoelectric material.

[0049] By testing its thermoelectric properties, the Seebeck coefficient and dimensionless thermoelectric figure of merit ZT of the thermoelectric material SnTe-y%Cu2Te are obtained, such as Figure 1 (a, b) As shown. It can be seen that after Cu2Te solid dissolves SnTe, it is beneficial to optimize the thermoelectric performance, and when the solid solubility is 5%, the effect of improving the ZT value is the best. Therefore, in the next step, we choose SnTe-5%Cu2Te as the matrix material in the Cu and Y co-doped SnTe system.

[0050] Experimental Example (II): Sn 1-x Y x Screening of Te-5%Cu2Te

[0051] In order to compare the chemical properties of the materials of the present invention, for the SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure, the chemical formula is Sn 1-x Y x Te-5%Cu2Te (x=0, 0.01, 0.03, 0.05, 0.07), according to the following preparation method, different concentrations of Sn 1-x Y x Te-5%Cu2Te bulk material, the preparation method is as follows:

[0052] S1: In an inert gas environment according to the chemical formula Sn 1-x Y x The metal single substance raw materials Te, Sn, Cu and Y are weighed in the stoichiometric ratio of Te-5%Cu2Te, and the purity of each metal single substance is not less than 99.999%. Then, the single substance materials are mixed evenly and transferred to a quartz tube, and the tube is flame-sealed using a hydrogen-oxygen machine in a vacuum environment with an absolute vacuum degree of no more than 0.1Pa; S2: the vacuum-sealed quartz tube in S1 is heated from room temperature to 1273K in a box furnace within 8 hours, and kept warm for 10 hours. After the insulation is completed, it is immediately quenched with water to room temperature to obtain an ingot; S3: the ingot of S2 is reheated again and subjected to high-temperature annealing. The annealing process includes: within 5 hours, the quartz tube is heated from room temperature to 923K, kept warm for 3 days, and then cooled to room temperature; S4: the ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintered under absolute vacuum, at a sintering temperature of 823K, a pressure of 50MPa, and a time of 5min to obtain a high-density SnTe-based bulk thermoelectric material.

[0053] The X-ray diffractometer (XRD) was used to analyze the Sn 1-x Y x Phase analysis of Te-5%Cu2Te thermoelectric material, such as Figure 2 As shown, the ordinate Intensity represents the intensity of the diffraction peak, and the abscissa 2θ represents the angle of the diffraction peak. By comparing with the standard PDF card of SnTe, it can be seen that the diffraction peak shows a single-phase behavior, and the main phase can be attributed to the SnTe cubic structure. In addition, a small amount of Y2Te3 impurity phase appears in the highly doped Y (x ≥ 0.03) sample, which can be further proved by SEM and EDS analysis.

[0054] The electrical properties of bulk thermoelectric materials were tested at 50-550°C using a thermoelectric properties evaluation device (CTA-3) to obtain the corresponding resistivity and Seebeck coefficient. The test results are as follows: Figure 3 , Figure 4 As shown in Figure 2, the resistivity and Seebeck coefficient of the doped material both increase with the increase of Y doping amount. The increase in resistivity is caused by the decrease in hole carrier concentration, as shown in Figure 2. Figure 5 As shown in Figure 2, the increase in the Seebeck coefficient is due to the convergence of the valence band to a certain extent. However, when Y reaches the solid solubility limit, the Seebeck coefficient decreases with the formation of impurity phases.

[0055] The power factor (PF) characterizes the electrical transmission capability of thermoelectric materials, such as Figure 6 As shown, the ordinate PF represents the power factor, and the abscissa T represents the temperature. After doping, due to the influence of general conductivity and high Seebeck coefficient, a higher power factor is finally obtained, showing the good electrical transmission performance of the thermoelectric material.

[0056] For Sn in the embodiment 0.97 Y 0.03 The free fracture surface morphology of the Te-5%Cu2Te thermoelectric compound bulk material sample was analyzed. Figure 7 As shown, Figure 7 (b) and (d) are Figure 7 (a) and (c) are high magnification images. Figure 7 (a) and (b) show that when the Y content exceeds the solid solubility limit, a nano-second phase with uniform size (50-100nm) is precipitated in situ at the grain boundary of the SnTe matrix. EDS analysis shows that the main component of these nanostructured aggregation areas is the Y2Te3 phase, and the other areas are Sn 0.97 Y 0.03 Te-5%Cu2Te matrix. At the same time, more refined Y2Te3 nanostructures (10-20nm) were observed on the surface of these nano-scale Y microstructures. No similar microstructures were found in low Y doping amounts. The present invention can control the content of doping elements to effectively adjust the microstructure of SnTe-based thermoelectric materials.

[0057] The thermal conductivity of the bulk material was tested at 50-550°C using a laser thermal conductivity meter model LFA457 produced by NETZSCH, Germany. The thermal conductivity of samples with different Y doping concentrations changes with temperature as shown in Figure 2. Figure 8 As shown, it can be seen that after Y doping, the total thermal conductivity κ tot This decrease is attributed to the lighter and smaller Y 3+ Enter Sn 2+ When the Y2Te3 has a supersaturated solid solubility, the phonon scattering process is intensified due to the mass fluctuation and lattice distortion. 1-x Y x The total thermal conductivity of Te-5%Cu2Te alloy (x=0.03, 0.05, 0.07) is reduced more than that of the light alloy sample (x=0.01). Among them, at 823K, when the Y doping amount is 5%, the lattice thermal conductivity reaches the minimum value of 0.43Wm -1 K -1 This special in-situ multi-scale nanocomposite structure greatly enhances the range of phonon scattering, causing more frequency types of phonons to be blocked by this special structure, thereby significantly reducing the lattice thermal conductivity of the material.

[0058] By testing the electrical and thermal conductivity, the Sn of the thermoelectric material can be calculated. 1-x Y x The dimensionless thermoelectric figure of merit ZT of Te-5%Cu2Te is Fig. 9As shown in the figure. The thermoelectric figure of merit after Y doping on the basis of SnTe copper alloying has shown a great improvement. At 823K, the ZT value reaches 1.27, which is a significant improvement of nearly 217% compared with the intrinsic SnTe thermoelectric material. Therefore, it has a strong application prospect.

[0059] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure, characterized in that: The following steps are involved: S1: Under inert gas protection, chemical formula Sn 1-x Y x The stoichiometric ratio of Te-5%Cu2Te is as follows: Weigh the metal raw materials Te, Sn, Cu and Y, where: x Take 0.03, 0.05 or 0.07, then mix the individual materials evenly and transfer them to a quartz tube, and use a hydrogen-oxygen machine to flame-seal the tube in a vacuum environment, wherein the purity of each metal element is not less than 99.999%; S2: Under vacuum conditions, the quartz tube vacuum-packed in S1 is heated in a box furnace to allow the raw materials to fully react in a high-temperature molten state. The process conditions for fully reacting in a high-temperature molten state include: within 6 to 8 hours, the temperature in the quartz tube is raised from room temperature to 1200K to 1300K, and the temperature is kept for 8 to 12 hours. After the temperature is kept, the ingot is immediately placed in supersaturated salt water at room temperature for quenching to obtain an ingot; S3: Under vacuum conditions, the ingot of S2 is reheated for high temperature annealing. The annealing process includes: heating the quartz tube from room temperature to 900-950K within 3-5 hours, keeping the temperature for 1-3 days, and then cooling it down to room temperature; S4: The ingot obtained in S3 is fully ground into fine powder, and then spark plasma sintering is performed under certain conditions. The spark plasma sintering process includes: evacuating the reaction system, and then sintering for 3 to 10 minutes under Ar protection at a temperature of 773K to 823K and a pressure of 45 to 55MPa to obtain a high-density bulk SnTe-based thermoelectric material.

2. The method for preparing SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure according to claim 1, characterized in that: In S2, the process conditions for sufficient reaction in a high-temperature molten state include: heating the temperature in the quartz tube from room temperature to 1273K within 8 hours, keeping the temperature for 10 hours, and immediately placing it in a supersaturated saline solution at room temperature for quenching after the end of the heat preservation.

3. The method for preparing SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure according to claim 1, characterized in that: The annealing process includes: heating the quartz tube from room temperature to 923K within 5 hours, keeping the temperature for 3 days, and then cooling it down to room temperature.

4. The method for preparing SnTe-based high-performance thermoelectric material with a multi-scale nanocomposite structure according to claim 1, characterized in that: In S4, the spark plasma sintering process includes: evacuating the reaction system, and then sintering for 5 minutes under Ar protection at a temperature of 823K and a pressure of 50MPa.

Citation Information

Patent Citations

  • Environmental-friendly tin telluride-based thermoelectric material and preparation method thereof

    CN106904972A